Domestic greywater treatment by electrocoagulation using hybrid electrode combinations. (April 2016) - Barışçı, Sibel; Turkay, Ozge
Abstract: Greywater (GW) treatment by the electrocoagulation (EC) process was investigated in this study. Eight different electrode combinations were evaluated. The effect of such important parameters as current density, initial pH (pHi ) and supporting electrolyte concentration (SEC) on the GW treatment by EC were researched. The highest COD removal was obtained with the Al–Fe–Fe–Al hybrid combination. Current density of 1 mA/cm 2 provided the highest efficiency. Further increase of current density did not show better performance. The original pH value (7.62) was found to be the most suitable condition. SEC did not affect the removal efficiencies. The EC process showed good performance to treat GW and provided allowable limits to reuse. The energy consumption was 9.46 kWh/m 3 for optimum conditions.